TEACHER SATISFACTION AND PERFORMANCE REVIEWED FROM THE PERSPECTIVE OF LEADERSHIP STYLE, WORK ENVIRONMENT, AND ORGANIZATIONAL CULTURE - Rizaldi Putra; Tengku Akmaruddin; Ikas Miran; Yutiandry Rivai; Saipul Al Sukri (Procuratio : Jurnal Ilmiah Manajemen, 2025)
The purpose of this study is to examine how organizational culture, work environment, and leadership style affect teachers' job satisfaction and performance. This research is quantitative in nature. Teachers at the Kerinci Citra Kasih Foundation in Pangkalan Kerinci made up the study's population. There were 85 responders in all, and the saturated sample method was utilized for sample selection. One technique for analyzing the data was Structural Equation Modeling (SEM). The findings demonstrated that leadership style had a positive and significant impact on job satisfaction, that the work environment had a positive and significant impact on job satisfaction, that organizational culture had no considerable impact on job satisfaction, that leadership style had a positive and significant impact on teacher performance, that organizational culture had no significant impact on teacher performance, and that job satisfaction had a positive and significant impact on teacher performance. Tujuan penelitian ini adalah untuk menguji pengaruh budaya organisasi, lingkungan kerja, dan gaya kepemimpinan terhadap kepuasan kerja dan kinerja guru. Penelitian ini bersifat kuantitatif. Populasi penelitian ini adalah guru-guru di Yayasan Kerinci Citra Kasih Pangkalan Kerinci. Jumlah responden keseluruhan 85 orang, dan metode sampel jenuh digunakan untuk pemilihan sampel. Salah satu teknik analisis data adalah Structural Equation Modeling (SEM). Hasil penelitian menunjukkan bahwa gaya kepemimpinan memiliki pengaruh positif dan signifikan terhadap kepuasan kerja, lingkungan kerja memiliki pengaruh positif dan signifikan terhadap kepuasan kerja, budaya organisasi tidak memiliki pengaruh yang cukup besar terhadap kepuasan kerja, gaya kepemimpinan memiliki pengaruh positif dan signifikan terhadap kinerja guru, budaya organisasi tidak memiliki pengaruh yang signifikan terhadap kinerja guru, dan kepuasan kerja memiliki pengaruh positif dan signifikan terhadap kinerja guru.